Antimicrobial Potential of Epiphytic Bacteria Associated With Seaweeds of Little Andaman, India - Karthick, Perumal; Mohanraju, Raju (Frontiers in Microbiology, 2018)
Seaweeds of the intertidal regions are a rich source of surface associated bacteria and are potential source of antimicrobial molecules. In the present study, 77 epiphytic isolates from eight different algae collected from Little Andaman were enumerated. On testing for their antimicrobial activities against certain pathogens twelve isolates showed positive and six of them showed significant antimicrobial inhibition zone against Shigella boydii type 1, Shigella flexneri type 2a, Shigella dysenteriae type 5, Enterotoxigenic E.coli O115, Enteropathogenic E.coli serotype O114, Vibrio cholera; O1 Ogawa, Aeromonas hydrophilla, Klebsiella pneumoniae, Staphylococcus aureus. Based on the activity these six isolates (G1C, G2C, G3C, UK, UVAD and Tor1) were identified by 16S rRNA gene sequence and were found to belong to the phyla Firmicutes and Proteobacteria. Purified antimicrobial compounds obtained from these isolates were identified by GC-MS. Furan derivatives were identified from G2C Pseudomonas stutzeri KJ849834, UVAD Alcanivorax dieselolei KJ849833, UK Vibrio sp KJ849837, Tor1 Exiguobacterium profundum KJ849838. While 2-Pyrrolidinone, Phenol, 2, 4-bis (1, 1-dimethylethyl) were from G3C Vibrio owensii KJ849836 and (1-Allylcyclopropyl) methanol from the extracts of G1C Bacillus sp. KJ849835. The results of the present study shows that these 6 potent isolates isolated from the seaweeds are found to be a source of antimicrobial compounds.